Diurnal and seasonal course of monoterpene emissions from Quercus ilex(L.) under natural conditions application of light and temperature algorithms - Bertin, N.; Staudt, M.; Hansen, U.; Seufert, G.; Foster, P.; Fugit, J. L.; Torres, L. (Atmospheric Environment, 1997)
Quercus ilex is a common oak species in the Mediterranean vegetation and a strong emitter of monoterpenes. Since the short-term control of monoterpene emissions from this species involved both temperature and light, the usual exponential function of temperature may not be sufficient to model the diurnal and seasonal emission course. In the frame of the BEMA-project (Biogenic Emissions in the Mediterranean Area), we investigated the tree-to-tree, branch-to-branch, diurnal, and seasonal variability of monoterpene emissions from Q. ibex over one and a half years at Castelporziano (Rome, Italy). In addition, w,: checked the suitability of the model developed for isoprene by Guenther et al. (1991, 1993) to simulate the short- and long-term variations of monoterpene emissions from this particular species. We found that the tree-to-tree variability was rather small compared to the experimental error during air sampling and analysis by diverse laboratories. The branch-to-branch variability was noticeable between sun- and shade-adapted branches only. 80% of total emissions were represented by cc-pinene, B-pinene and sabinene, whose proportions were stable over the year and independent of light exposure. The emission factor (emission rate at 30°C and 1000 ~molphotonm-Zs-l ) estimated by the isoprene model or extrapo- lated from measurements was similar: it was about 22 pggdw -r h-r for sun-exposed branches and 2.3 pggdw.-’ h-r for shade-adapted branches. It was rather stable over the seasons except during leaf development. The diurnal and seasonal emission patterns from Q. ibex were simulated in a satisfying way by Guenther’s algorithms especially if we excluded the laboratory variability. For shade-adapted branches, an emission factor 17 times lower had to be applied, but temperature and light responses were unchanged.
Keywords: Holm oak; index; light and temperature algorithm; Mediterranean vegetation; Modelling; Monoterpene; Quercus ilex

The terpenoid emission pattern of Quercus coccifera L coincides with the emission pattern found with Quercus ilex L - Hansen, U.; Seufert, G. (PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION, 1997)
Monoterpene and isoprene emission rates from Kermes or Holly oak (Quercus coccifera L.), an evergreen shrub or small tree which is widely present in the Mediterranean area, were investigated in a greenhouse using a dynamic enclosure technique, Monoterpenes emitted with the highest rates from Quercus coccifera were alpha-pinene, sabinene and beta-pinene. alpha-pinene contributed 41 % to the total monoterpene emission, sabinene 28 % and beta-pinene 25 %. The isoprene emission rate was 0.7 % of the total monoterpene emission rate. Standardisation to 30 degrees C revealed a total monoterpene emission rate of 18.7 mu g gLDW(-1) h(-1). The data show that terpenoid emissions from Kermes oak (Quercus coccifera L.) are qualitatively and quantitatively similar to those of Helm oak (Quercus ilex L.). Both species have to be considered as strong monoterpene emitters, Emissions are considerably higher compared to the emission factor of 1.2 mu g C gLDW(-1) h(-1) which was assumed to represent the monoterpene emission rate from Mediterranean ecosystems at standard conditions in a study about a global model of natural VOC emissions.
The following values have no corresponding Zotero field: periodical: PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION pub-location: ASHURST LODGE, SOUTHAMPTON, HANTS, ENGLAND S04 2AA
Keywords: alpha-pinene; beta-pinene; isoterpene; Mediterranean area; Monoterpene; Quercus coccifera L.; sabinene; terpenoid; VOC emissions